Back Cover Image, Volume 92, Number 12, December 2020. Issue 12 (5th November 2020) - Paniz‐Mondolfi, Alberto E.; van den Akker, Tayler; Márquez‐Colmenarez, Marilianna C.; Delgado‐Noguera, Lourdes A.; Valderrama, Omar; Sordillo, Emilia M.
Abstract : Back Cover Caption : The cover image is based on the Review Kawasaki Disease Seasonality in Venezuela Supports an Arbovirus Infection Trigger by Alberto E. Paniz‐Mondolfi et al., https://doi.org/10.1002/jmv.26381 .